2012
DOI: 10.1016/j.biopsycho.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in sleep architecture: The role of ethnic discrimination

Abstract: African Americans have been consistently shown to have less deep (slow wave sleep; SWS) and more light (Stages 1 and 2) sleep than Caucasian Americans. This paper explored whether discrimination, a stressor that uniquely impacts certain ethnic groups, contributes to differences in sleep architecture. The sleep of 164 African and Caucasian Americans was examined with laboratory based polysomnography (PSG). Experiences of perceived discrimination (The Scale of Ethnic Experience) and sociodemographic factors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 36 publications
11
94
1
Order By: Relevance
“…Future studies should studies, 1 and symptom severity was lower than commonly reported. In addition, there was no difference between African Americans and Whites on RLS measures, which agrees with some studies 14,15,31,32 but not all. 11,33 Given that there is a link between sleep problems and health outcomes, we also explored the relationship of sleep with disability.…”
Section: Discussionsupporting
confidence: 91%
“…Future studies should studies, 1 and symptom severity was lower than commonly reported. In addition, there was no difference between African Americans and Whites on RLS measures, which agrees with some studies 14,15,31,32 but not all. 11,33 Given that there is a link between sleep problems and health outcomes, we also explored the relationship of sleep with disability.…”
Section: Discussionsupporting
confidence: 91%
“…In this latter case, the publications confirm and of two and up to three times in the emergence of sleep problems, such as apnoea, storing and insomnia among smokers (8,10,23) . Another important detail is that these findings were also repeated with samples of adults, pregnant women, adolescents and children (24)(25) .…”
Section: Discussionmentioning
confidence: 58%
“…In the current study, we focus specifically on adolescents’ experiences of discrimination as an important type of stressor that can compromise sleep. Many studies that have examined the impact of discrimination on sleep have focused on adult populations, rather than adolescents (e.g., Grandner et al, 2012; Slopen & Williams, 2014; Tomfohr, Pung, Edwards, & Dimsdale, 2012). Of the few studies that have recently focused on discrimination and sleep during adolescence, researchers found that ethnic discrimination was related to poor sleep quality and shorter sleep duration (Huynh & Gillen-O’Neel, 2013; Yip, 2015).…”
Section: Introductionmentioning
confidence: 99%